2012
DOI: 10.1523/jneurosci.3753-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor-Dependent Synaptic Activation of TRPC Channels in Olfactory Bulb Granule Cells

Abstract: TRPC channels are widely expressed throughout the nervous system including the olfactory bulb where their function is largely unknown. Here we describe their contribution to central synaptic processing at the reciprocal mitral and tufted cell - granule cell microcircuit, the most abundant synapse of the mammalian olfactory bulb. Suprathreshold activation of the synapse causes sodium action potentials in mouse granule cells and a subsequent long-lasting depolarization (LLD) linked to a global dendritic postsyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 72 publications
5
47
0
Order By: Relevance
“…In agreement with this idea, compound mice lacking Trpc1 and Trpc4 lacked epileptiform bursting secondary to metabotropic glutamate receptor activation in hippocampal CA1 neurons (Phelan et al 2013) or suppressed by 74 % in lateral septal neurons in single Trpc1 mutant mice (Phelan et al 2012). Similar effects were seen in olfactory granule cells (Stroh et al 2012). Following previous cell culture work (Ma et al 2003), Ong et al showed that TRPC1-enhanced store-operated currents in myeloid precursors and mice lacking Trpc1 showed a modest decrease in osteoclastogenesis and an increase in bone mass (Ong et al 2013).…”
supporting
confidence: 65%
“…In agreement with this idea, compound mice lacking Trpc1 and Trpc4 lacked epileptiform bursting secondary to metabotropic glutamate receptor activation in hippocampal CA1 neurons (Phelan et al 2013) or suppressed by 74 % in lateral septal neurons in single Trpc1 mutant mice (Phelan et al 2012). Similar effects were seen in olfactory granule cells (Stroh et al 2012). Following previous cell culture work (Ma et al 2003), Ong et al showed that TRPC1-enhanced store-operated currents in myeloid precursors and mice lacking Trpc1 showed a modest decrease in osteoclastogenesis and an increase in bone mass (Ong et al 2013).…”
supporting
confidence: 65%
“…In the lateral geniculate nucleus, 5HT activates TRPC4 channels, causing sufficient calcium influx to mediate action potential-independent GABA release (Munsch et al 2003). TRPC channels are also involved in action potential-independent signaling at dendrodendritic synapses between granule and MCs (Stroh et al 2012). Thus TRP-mediated mechanisms may be a common target of neuromodulator transmitter action at dendrodendritic synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Our interest in elucidating the function of TRPC channels in neural progenitor migration as well as the current lack of specific channel blockers for the TRPCs led us to use TRPCdeficient C57 mice. TRPC1/TRPC4/TRPC5-deficient mice (1/ 4/5 TKO) [24] and TRPC3/TRPC6-deficient mice (3/6 DKO) have been described [25]. All TRPC-deficient mice were from a mixed C57 genetic background.…”
Section: Micementioning
confidence: 99%